Pengalaman Remaja Perempuan Melakukan Deliberate Self-Harm (DSA): Sebuah Kajian Fenomenologis - Andi Tenri Faradiba; Zainal Abidin (Bulletin of Counseling and Psychotherapy, 2022)
Self harm or Deliberate Self-Harm (DSH) is carried out with the intention of intentionally injuring a member of the body without any suicidal intent. Previous research has stated that adolescent girls are the most vulnerable group to DSH. DSH behavior in adolescence that is repeated with increasing intensity increases the risk of suicide in adulthood. This research was conducted to find out how the first experience of DSH behavior was carried out by female adolescents and how self-harm was used. A qualitative approach with the type of generic qualitative study is carried out to answer these questions. Participants were selected by snowball sampling technique with the characteristics of female adolescents aged 12-23 years and had DSH in the last three months. Data were collected and processed using thematic analysis. The results show that the teenage girls in this study have been doing self-harm for more than five years and it begins by looking at social media which shows that self-harm can be a solution to the problems they face. The methods of self-harm and the depth of injury that arise due to DSH behavior are increasingly varied and increase the risk for the perpetrator. DSH behavior is important to pay attention to considering the risks and dangers it poses and has the potential to increase the possibility of suicide.